Not a Black and European-Americans question: how are investor behavior and perceptions related to race and ethnicity? - Hira, Tahira K.; Sabri, Mohamad Fazli; Loibl, Caezilia (Malaysian Consumer and Family Economics Association, 2015)
This paper explores racial/ethnical differences among investors’ risk tolerance, confidence, and asset ownership. The data for this study is derived from a national telephone survey conducted at a regional Midwest university. The data collection began by purchasing 7,500 phone numbers from Survey Sampling International. Potential households were selected by targeting phone numbers from the sample in geographical areas with average household incomes of $100,000 per year or higher. Results show that among higher income investors, African-Americans were less likely to invest in corporate stocks and bonds; Asian-Americans expressed particularly high investor confidence and had a preference for purchasing Certificates of Deposit (CDs); Hispanic-Americans expressed significantly lower risk tolerance and lower holdings of corporate stocks. These findings indicate that community-based financial education should be aware of these racial/ethnic characteristics and aim to tailor educational interventions to it, where possible. These findings offer valuable insights to educators, financial planners and financial 115 institutions offering these products.